Reconfigurable nanoscale soft materials. Issue 1 (February 2019) - Ou, Zihao; Kim, Ahyoung; Huang, Wen; Braun, Paul V.; Li, Xiuling; Chen, Qian
Highlights: Recent progress on using liquid-phase TEM to study reconfigurable nanomaterials. New strategies to promote reconfigurability at the nanoscale. Designing shape-shifting colloids responsive to external stimulus. Utilizing flexible electronic substrates as reconfigurable platforms. Abstract: We discuss recent research efforts towards understanding and implementing the physical rules needed to make materials—especially materials composed of nanoscale building blocks—that exhibit the defining characteristics of living systems: adaptive and evolving functional behavior. In particular, we highlight advancements in direct imaging and quantifying of kinetic pathways governing structural reconfiguration in model systems of colloidal nanoparticles as well as emerging opportunities brought by frontier efforts in synthesizing shape-shifting colloids and flexible electronics. Direct observation of kinetic "crossroads" in nanoparticle self-assembly and reconfiguration will offer insight into how these steps can be manipulated to design dynamic, potentially novel materials and devices. Moreover, these principles will not be limited to nanoparticles; when extended to building blocks like soft micelles and proteins, they have the potential to have a similar impact throughout the broader field of soft matter physics.